Hypertension screening in truck drivers - Taraghi Z; Ilali E (Tehran University of Medical Sciences, 2004)
Introduction: Hypertension is a major risk factor for coronary heart disease. Truck drivers are more exposed to hypertension due to sedentary life style and consequent obesity, improper food, job stress and high prevalence of cigarette smoking. Materials and Methods: In this study, after completing a questionnaire by interview, the blood pressures of 122 members of union of truck drivers of Sari, Northern Iran, were measured in two separate occasions. Measurement of blood pressure in all drivers was performed from right arm by using a digital automatic OMRON sphygmomanometer. In order to measure correctly, guidelines of American Heart Association were noted. Analyze of data was performed by SPSS software and descriptive statistics such as mean, standard deviation and Pearson correlation were used. Results: Analyze of data showed that most of truck drivers (59.1%) were overweight and 14.8% of them were obese. Mean of BMI was 25.5 (standard deviation 4.65). Around 48.3% were smoker, 61.5% didn't have physical activity and 36.9% had hypertension, which was mostly mild to moderate. Mean systolic blood pressure was 135.08 (standard deviation 17.44) and mean diastolic blood pressure was 82.86 (standard deviation 8.16). Seventy seven percent of hypertensive patients were not aware of their problem. Statistical tests showed that there was a significant correlation between job history, BMI and hypertension. Conclusion: Regarding high incidence of hypertension in truck drivers, it seems that similar studies must be done in other long-distance drivers, such as bus drivers, and their blood pressures must be assessed at least once a year.